(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article presents a cross-cultural analysis of psychological support strategies for adolescents with disabilities, based on the experiences of various countries, particularly Scandinavian states, Japan, and the United States. The study highlights how cultural values, societal attitudes toward disability, and inclusive policies in education systems directly influence the degree to which emotional stress is mitigated. Furthermore, the psychological condition of adolescents with disabilities is examined within the context of Uzbekistan, focusing on the influence of prevailing mentalities and traditional beliefs. The article substantiates the need to develop a national psychological approach and inclusive strategies grounded in digital technologies, adapted to Uzbekistan’s unique socio-cultural environment.